Dummies and the sudden infant death syndrome. Issue 4 (April 1993) - Mitchell, E A; Taylor, B J; Ford, R P; Stewart, A W; Becroft, D M; Thompson, J M; Scragg, R; Hassall, I B; Barry, D M; Allen, E M
Abstract : The association between dummy use and sudden infant death syndrome (SIDS) was investigated in 485 deaths due to SIDS in the postneonatal age group and compared with 1800 control infants. Parental interviews were completed in 87% of subjects. The prevalence of dummy use in New Zealand is low and varies within New Zealand. Dummy use in the two week period before death was less in cases of SIDS than in the last two weeks for controls (odds ratio (OR) 0.76, 95% confidence interval (CI) 0.57 to 1.02). Use of a dummy in the last sleep for cases of SIDS or in the nominated sleep for controls was significantly less in cases than controls (OR 0.44, 95% CI 0.26 to 0.73). The OR changed very little after controlling for a wide range of potential confounders. It is concluded that dummy use may protect against SIDS, but this observation needs to be repeated before dummies can be recommended for this purpose. If dummy sucking is protective then it is one of several factors that may explain the higher mortality from SIDS in New Zealand than in other countries, and may also explain in part the regional variation within New Zealand.